2021
DOI: 10.1002/ca.23719
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular joint anatomy: Ultrasonographic appearances and sexual dimorphism

Abstract: Introduction Temporomandibular joint (TMJ) dysfunction is common, with a greater prevalence in females. While magnetic resonance imaging (MRI) is commonly used for clinical investigation, ultrasonography represents a potential alternative in some clinical scenarios. We designed a protocol for ultrasonographic evaluation of the TMJ and assessed its reliability. Presentation was compared between the sexes to establish whether an anatomical dichotomy underlies the female preponderance of TMJ dysfunction. Material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Several factors may contribute to this discrepancy, including variations in hormone levels, 28–30 such as the influence of oestrogen on the development, healing and metabolism of TMJ 46,47 . Anatomical differences impacting joint biomechanics also play a crucial role 48,49 . For instance, male individuals exhibit distinct anatomical characteristics in their craniofacial structure, including longer, wider, and thicker maxillary bones, a more obtuse mandibular angle and a larger condylar head.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors may contribute to this discrepancy, including variations in hormone levels, 28–30 such as the influence of oestrogen on the development, healing and metabolism of TMJ 46,47 . Anatomical differences impacting joint biomechanics also play a crucial role 48,49 . For instance, male individuals exhibit distinct anatomical characteristics in their craniofacial structure, including longer, wider, and thicker maxillary bones, a more obtuse mandibular angle and a larger condylar head.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had indicated that HR-US with a frequency higher than 12 MHz could differentiate the tissues in more detail and therefore achieve better diagnostic performance ( 20 , 21 ). The transducer was normally placed anterior to the tragus and oriented horizontally or longitudinally ( 7 , 8 , 13 ). The horizontal scan can image the transversal slices of the anterosuperior articular compartment, and therefore is commonly adopted to evaluate the disc position relative to the condyle and articular eminence.…”
Section: Discussionmentioning
confidence: 99%
“…The objective methods based on the measurement of representative anatomical landmarks were proposed to detect intra-articular abnormalities indirectly ( 29 ). The measurement methods were applied to obtain the reference values of normal joints ( 13 , 30 ), as well as to evaluate their association with joint effusion ( 31 - 34 ), joint pain ( 35 ), juvenile idiopathic arthritis (JIA) ( 36 , 37 ), and DD ( 29 , 38 ). The lateral capsular width was the most frequently used variable to investigate structural abnormalities in these studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 , 5 , 8 - 12 However, very few studies have inspected the shape of the mandibular condyle with potential implications in clinical diagnosis and therapeutic planning. Although Computed Tomography (CT) scan and ultrasonography techniques are utilized for studying mandibular condyle morphology, 11 , 13 , 14 panoramic radiography is one of the most often utilized low-cost methods. 4 , 6 , 15 …”
Section: Discussionmentioning
confidence: 99%